1997
DOI: 10.3109/03630269708997382
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Hematological Response to Hydroxyurea in a Patient with Hb Leporbp-Thalassemia

Abstract: The possibility of increasing Hb F in vivo using drugs like 5-azacytidine, hydroxyurea, and butyrate has been established. However, in many cases this does not entail an increase in total hemoglobin. We report on a patient with Hb Lepore/beta-thalassemia being treated with hydroxyurea (30 mg/Kg/day) because of the presence of erythroid extramedullary masses with severe neurological abnormalities. During therapy the patient showed a remarkable improvement in neurological signs due to the reduction in extra-medu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Several reports confirmed the HbF augmenting effect of HU both in vitro and in vivo [94][95][96][97][98][99][100][101][102][103][104]. For example, Yavarian et al [105] reported the treatment with HU of 133 patients with transfusion-dependent β-thalassemia.…”
Section: Inducers Of Fetal Hemoglobinmentioning
confidence: 83%
“…Several reports confirmed the HbF augmenting effect of HU both in vitro and in vivo [94][95][96][97][98][99][100][101][102][103][104]. For example, Yavarian et al [105] reported the treatment with HU of 133 patients with transfusion-dependent β-thalassemia.…”
Section: Inducers Of Fetal Hemoglobinmentioning
confidence: 83%
“…44,49 Patients with Lepore or db-thalassaemia genotypes usually showed a better response. 50,61,90 Of note, several reports confirm that the effects of hydroxyurea in patients with hemoglobin S/b-thalassemia may be better than those even reported for homozygous hemoglobin S disease, because the synthesized g-chains not only inhibit the sickling process, but they also neutralize the noxious effects of the excess a-chains and cut down on ineffective erythropoiesis. [91][92][93][94][95] Co-inheritance of a-thalassemia was described as a predictor of good response in some studies, 44,77,96 but it was found to have no effect in others.…”
Section: Predictors Of Responsementioning
confidence: 94%
“…After early case reports documented hematological improvements in b-thalassemia patients treated with hydroxyurea, 51,[58][59][60][61][62][63][64] several studies evaluated the efficacy and safety of the drug in this patient population (Table 1). 44,49,50, These primarily included small single-arm trials or retrospective cohort studies.…”
Section: Hematological Outcomesmentioning
confidence: 99%
“…1 Multiple pharmacological agents able to increase HbF production have been investigated and hydroxyurea (HU) is the only inducer approved for the treatment of adult patients affected by sickle cell disease 2 which entered into clinical practice for β-thalassemia intermedia (β-TI). 3 However, there is a great variability in the response of patients after HU therapy, in fact some patients are good responders while others exhibit little or no change in HbF levels. 4,5 Moreover, in responder patients, a decrease in the efficacy during long-term treatment was observed.…”
Section: Introductionmentioning
confidence: 99%